Two new species of Dichorisandra (Commelinaceae) from Rio de Janeiro and comments on the two species included in Vellozo’s “Flora Fluminensis” - Aona, Lidyanne Yuriko Saleme; Bittrich, Volker; Amaral, Maria Do Carmo E. (Phytotaxa, 2014)
Two new species of Dichorisandra collected in Rio de Janeiro state are described based on studies in the field, herbarium specimens and cultivated plants. Dichorisandra odorata can be distinguished by its small stature, leaves congested at the apex of the stems, with the lamina densely pilose on both sides, fragrant flowers (unusual for the genus), six anthers with pilose connectives and dehiscent by an apical pore; Dichorisandra nana resembles D. thyrsiflora by the presence of six yellow anthers dehiscent by apical pores, however it differs being smaller, reaching only 30 cm tall, and by the position of the stamens in relation to the petals. Illustrations of the species, comparisons with species looking morphologically similar, discussion of the diagnostic characters, as well as their conservation status are presented. Vellozo´s Flora Fluminensis includes two names that belong to Dichorisandra, both treated under the genus Convallaria. The first one, C. diffusa, is a synonym of D. hexandra while the other, thought by Vellozo to be C. racemosa (= Maianthemum racemosum), is in fact D. thyrsiflora.